A survey of the trajectories conceptual framework: investigating theory use in HCI - Velt, Raphael; Benford, Steve; Reeves, Stuart (ACM, 2017)
We present a case study of how Human-Computer Interaction (HCI) theory is reused within the field. We analyze the HCI literature in order to reveal the impact of one particular theory, the trajectories framework that has been cited as an example of both contemporary HCI theory and a strong concept that sits between theory and design practice. Our analysis of 60 papers that seriously engaged with trajectories reveals the purposes that the framework served and which parts of it they used. We compare our findings to the originally stated goals of trajectories and to subsequent claims of its status as both theory and strong concept. The results shed new light on what we mean by theory in HCI, including its relationship to practice and to other disciplines.